(untitled) (International Journal of Statistical Sciences, 2026)
The mental health impact of the COVID-19 pandemic has been particularly pronounced among young individuals seeking employment. This study aimed to investigate the levels of depression, anxiety and stress among university students who completed their education and were actively job-seeking during the pandemic, along with identifying associated factors. A web-based cross-sectional study was conducted from January to November 2022, coinciding with the peak of COVID-19 cases in Bangladesh. The study included 607 university graduates actively seeking employment. Mental health status was assessed through depression, anxiety and stress. These were determined using the PHQ-9, GAD-7 and PSS-10 scales respectively. These mental health outcomes were considered outcome variables while socio-demographic characteristics of the respondents served as explanatory variables. Statistical analysis included chi-square tests to explore associations and binary logistic regression to identify significant predictors. The results showed that 50%, 39%, and 78% of respondents reported moderate-to-severe depression, anxiety and stress, respectively. Younger age (20–24 years) and male gender were significantly associated with poorer mental health outcomes. Residency in specific divisions such as Rangpur and Chattogram also showed significant associations. Furthermore, 43% of participants reported disrupted job searches and 84% faced setbacks in their career goals due to pandemic-related challenges. Academic disruptions also correlated with heightened mental health issues. A majority of university graduates actively seeking employment during the pandemic encountered moderate to severe levels of depression, anxiety and stress. These findings underscore the need for targeted mental health programs during pandemics and similar events in future. IJSS, Vol. 26(1), March, 2026, pp 25-37